2019
DOI: 10.1590/s1678-9946201961065
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus pulmonary syndrome in children: case report and case series from an endemic area of Brazil

Abstract: Hantavirus Cardiopulmonary Syndrome (HCPS) is an important emergent zoonosis associated with wild rodents in Brazil, where this viral infection in children is generally rare. We present HCPS in a child from the Pantanal Biome and a review of all reported pediatric cases in Mato Grosso State, an endemic area for HCPS in Brazil. The investigation used the Information System for Notifiable Diseases database (SINAN). A 12-year-old boy was hospitalized with fever and respiratory failure and hantavirus IgM and IgG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
4
0
3
Order By: Relevance
“…The median between onset of symptoms and death is 5 days in the Reyes series (49). In a study of 32 infected Brazilian children showed similar clinical manifestations to adults identifying the two phases, prodromal, with non-specific symptoms and the cardiopulmonary syndrome phase, where cough (46.9%) and dyspnea (59.4%) appears; 59.4% of these children were hospitalized and the CFR was 34.4%, like was described by Reyes (51). In countries such as Barbados where hantavirus infection is milder, the infection in children can occur as a non-specific febrile syndrome mistaken for arbovirus infections such as dengue (52).…”
Section: Clinical Manifestationsmentioning
confidence: 66%
See 1 more Smart Citation
“…The median between onset of symptoms and death is 5 days in the Reyes series (49). In a study of 32 infected Brazilian children showed similar clinical manifestations to adults identifying the two phases, prodromal, with non-specific symptoms and the cardiopulmonary syndrome phase, where cough (46.9%) and dyspnea (59.4%) appears; 59.4% of these children were hospitalized and the CFR was 34.4%, like was described by Reyes (51). In countries such as Barbados where hantavirus infection is milder, the infection in children can occur as a non-specific febrile syndrome mistaken for arbovirus infections such as dengue (52).…”
Section: Clinical Manifestationsmentioning
confidence: 66%
“…The laboratory findings include thrombocytopenia in 94.7%, hemoconcentration in 63.1%, left shift leukocytosis in 47.3%, and atypical lymphocytes in 26.3% (51).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Historically in LA, mining, gold panning and forestry were high-exposure occupations [28,29] due to their environmental impact, poor living conditions, remoteness and low access to health services. It is also important to highlight the relationship between malaria and gold mining/panning as a major source of disease in the areas where it is done, because the nature of the activity itself favors contact with and proliferation of mosquitoes [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Somando-se aos achados supracitados, o estudo de Santos et al (2019), no qual há o relato de 10 pacientes com SCPH que evoluíram para o óbito poucas horas ou dias após a admissão e que foram submetidos à necropsia entre os anos de 2000 e 2014, reforça o predomínio do sexo masculino com atividades relacionadas à área rural e contato prévio com roedores. Terças-Trettel et al (2019) analisaram dados secundários de casos de SCPH em crianças do MT, confirmados entre os anos 1999 e 2018, sendo 32 deles em menores de 14 anos. 84,4% dos casos de exposição das crianças ocorreram em casa durante a vida cotidiana, as condições de risco mais relatadas foram o contato com casos humanos em suas famílias (56,2%), presença ou participação na limpeza da casa (50%) e contato direto com roedores (40,6%).…”
Section: Epidemiologiaunclassified
“…A fase prodrômica, com duração de 3 a 4 dias, clinicamente apresenta sintomas pouco específicos como vômito, tontura, tosse não produtiva e náuseas (RUPASINGHE et al, 2021). Terças-Trettel et al (2019) relataram que a sintomatologia mais comumente descrita abrangia febre (75%), dispneia (59,4), tosse (46,9%), cefaleia (43,7%) e dor abdominal (43,7%). Em consonância, Santos et al (2019) concluíram que febre (80%), dispneia (90%) e mialgia (70%) estiveram presentes na análise dos pacientes em estudo.…”
Section: Diagnóstico Clínicounclassified